HBR guide to getting the right work done (Harvard Business Review Press, 2012)
In the HBR Guide to Getting the Right Work Done, you’ll discover how to focus your time and energy where they will yield the greatest reward. Not only will you end each day knowing you made progress―your improved productivity will also set you apart from the pack.